Bureaucrats in business : economics and politics of government ownership : summary (World Bank WashingtonUS, 1995)
Focuses on which types of state enterprise reform measures have worked best. Describes the obstacles governments face when attempting to divest state-owned enterprises. Seeks to determine how contracts between management and government can serve as tools to reform enterprises.
DC